Housing, Energy Cost, and the Poor: Counteracting Effects in Germany's Housing Allowance Program - Peter Grösche (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Adequate housing and affordable warmth are essential human needs, the lack of which may seriously harm people's health. Germany provides an allowance to low-income households, covering the housing as well as the space heating cost, to protect people from the consequences of poor housing conditions and fuel poverty. In order to limit public expenditures, payment recipients are required to choose low-cost dwellings, with the consequence that they probably occupy flats with a poor thermal performance. Recipients are thus likely to have a higher energy consumption and energy expenditures. Using a large data set of German households, this paper demonstrates that this counteracting effect is of negligible magnitude. Yet, from an ecological perspective, the allowance scheme creates distorted incentives and should be reformed.
Keywords: C33; H53; Q48; 330; Housing Allowance; Energy Efficiency; Simultaneous-Equation System